Symmetry properties and exact solutions of the time fractional Kolmogorov-Petrovskii-Piskunov equation - Hashemi, M. S.; İnç, Mustafa; Bayram, M. (Soc Mexicana Fisica, 2019)
In this paper, the time fractional Kolmogorov-Petrovskii-Piskunov (TFKPP) equation is analyzed by means of Lie symmetry approach. The TFKPP is reduced to ordinary differential equation of fractional order via the attained point symmetries. Moreover, the simplest equation method is used in construct the exact solutions of underlying equation with recently introduced conformable fractional derivative.
Keywords: Time fractional Kolmogorov-Petrovskii-Piskunov equation; Lie symmetry analysis; Erdelyi-Kober fractional derivative; Riemann-Liouville derivative; conformable fractional derivative; simplest equation method